2021
DOI: 10.3390/sym13091697
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Start Algorithm for Solving the Capacitated Vehicle Routing Problem with Two-Dimensional Loading Constraints

Abstract: This work presents a multistart algorithm for solving the capacitated vehicle routing problem with 2D loading constraints (2L-CVRP) allowing for the rotation of goods. Research dedicated to graph theory and symmetry considered the vehicle routing problem as a classical application. This problem has complex aspects that stimulate the use of advanced algorithms and symmetry in graphs. The use of graph modeling of the 2L-CVRP problem by undirected graph allowed the high performance of the algorithm. The developed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…As the database used is quite unbalanced, the stratified cross-validation was run in all experiments with the different hyperparameters to ensure more consistent results. Other scenarios and applications described can be found in [18]. Thus, after k executions, reference [9] defines that the total number of correctly classified instances is divided by the total number of instances N, resulting in an overall accuracy of the model.…”
Section: Model Training and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the database used is quite unbalanced, the stratified cross-validation was run in all experiments with the different hyperparameters to ensure more consistent results. Other scenarios and applications described can be found in [18]. Thus, after k executions, reference [9] defines that the total number of correctly classified instances is divided by the total number of instances N, resulting in an overall accuracy of the model.…”
Section: Model Training and Validationmentioning
confidence: 99%
“…As the database used is quite unbalanced, the stratified cross-validation was run in all experiments with the different hyperparameters to ensure more consistent results. Other scenarios and applications described can be found in [18].…”
Section: Model Training and Validationmentioning
confidence: 99%
“…As the database used is quite unbalanced, the stratified cross-validation was run in all experiments with the different hyperparameters, to ensure more consistent results. There are other scenarios and applications as described in [25].…”
Section: Model Training and Validationmentioning
confidence: 99%
“…For that purpose, they studied multi-core processors as well as graphics processing units and concluded that the parallelization resources are efficiently utilized. Multi-threading in a multi-core system was utilized in the multi-start approach [27]. Other researchers studied used protocol for data transmission between different nodes in a network, such as Huang et al [28].…”
Section: Introductionmentioning
confidence: 99%